THE SEMANTIC SHIFT OF HONORIFIC ADDRESS TERMS FOR ISLAMIC RELIGIOUS LEADERS IN INDONESIA: A SOCIOLINGUISTIC PERSPECTIVE - Fauzia Fahmi Yuniarti Nasution; Ahmad Nafi’ul Walid (Universitas Negeri Medan, 2026)
This study aims to examine the semantic shift of honorific address terms used to refer to Islamic religious leaders in Indonesia from a sociolinguistic perspective. Honorific address terms represent a form of language variation that functions not only as a means of communication but also as a marker of social relations, authority, and cultural–religious values within society. This research employs a qualitative descriptive approach with a library research method. The data consist of linguistic units in the form of words and phrases functioning as honorific address terms, collected from various written and online sources, including books, scholarly journal articles, previous studies, and official religious and institutional websites. Data analysis was conducted using Miles and Huberman’s interactive model, which includes data reduction, data display, and conclusion drawing. The findings indicate that there are diverse honorific address terms for Islamic religious leaders in Indonesia, varying according to regional and cultural backgrounds, such as kyai, buya, ajengan, tengku, tuan guru, and gurutta. Most of these terms have undergone a semantic shift from kinship or aristocratic meanings to religious honorific titles through mechanisms of metonymy, social legitimation, and local cultural traditions. This semantic shift highlights the close relationship between language, culture, and socio-religious structures in Indonesian Muslim society.